Programming Technologies for Social Inclusion With Scratch: Computational Practices in a Teacher’s Professional Development Course - Monjelat, Natalia (Revista Electrónica Educare, 2019)
In recent years, there is an interest in developing practices, concepts and perspectives of computational thinking and programming in schools. Therefore, it is crucial to train teachers in these subjects. However, little is known about the process that teachers follow when approaching these new contents. In this context, the present exploratory and intrinsic case study aims to analyze the computational thinking practices developed by a group of 13 teachers while participating in a professional development workshop, where they created technologies for social inclusion (TIS) by programming with Scratch. The analysis of the different data collected during this pilot experience (surveys, productions carried out by the participants, audio recordings, etc.) evidences a close articulation between computational practices and programming of hypermedia projects that addresse participants’ contextualized problematics. These results show that professional development related to programming was proposed as a process close to the day-to-day reality of teachers, highlighting the importance of generating mediated and situated educational practices. Designing a training path to create TIS appears, in this sense, as a valid option for the teaching of programming and the development of computational thinking, in line with previous studies that proposed professional development courses for teachers from contextualized proposals, and using significant examples in a community and collaborative framework of reflection and exchange.